Highly Stable and Efficient Lignin‐PEDOT/PSS Composites for Removal of Toxic Metals. (4th December 2017) - Checkol, Fekadu; Elfwing, Anders; Greczynski, Grzegorz; Mehretie, Solomon; Inganäs, Olle; Admassie, Shimelis
Abstract: A hybrid biopolymer/electronic polymer electrode is demonstrated here to extract metal ions, in this case lead, from water. The hybrid material consists of poly(3, 4‐ethylenedioxythiophene)/polystyrene sulfonate (PEDOT/PSS) and the biopolymer lignin (LG) and is prepared by a simple one‐step galvanostatic polymerization from aqueous solution. The hybrid material is characterized by cyclic voltammetry, electrochemical quartz microbalance, X‐ray photoelectron spectroscopy, and scanning electron microscopy techniques. The electrochemical and spectroscopic results confirm that lead ions can be adsorbed on the composites films from a neutral solution of lead ions by applying a negative potential and subsequently desorbed from the hybrid films by applying positive potential. The adsorption capacity for lead ions on PEDOT/PSS is 245.5 mg g −1 and is almost doubled to 452.8 mg g −1 by incorporating LG into PEDOT/PSS. Abstract : A network of conducting and biopolymer is prepared by simple galvanostatic polymerization for removal of toxic metal ions such as lead from aqueous solution. The composite material is an efficient, stable, scalable, and reusable material which does not require chemicals for regeneration.